Sitagliptin mitigates hypoxia/reoxygenation (H/R)-induced injury in cardiomyocytes by mediating sirtuin 3 (SIRT3) and autophagy. Issue 5 (2nd May 2022) - Yang, Mao; Xi, Ningning; Gao, Meng; Yu, Yanwei
ABSTRACT: Potential ischemia/reperfusion (I/R) injuries are commonly induced during treatment of cardiovascular diseases, such as acute myocardial infarction (AMI). It is reported that oxidative stress and over-autophagy in cardiomyocytes are involved in the pathogenesis of I/R injury. Sitagliptin is an effective inhibitor of dipeptidyl peptidase 4 (DPP-4) for the treatment of diabetes, which is recently reported to regulate oxidative stress and autophagy. The present study is designed to explore the function of Sitagliptin on I/R injury. Hypoxia/reoxygenation (H/R) condition was used to simulate the I/R injury on cardiomyocytes. We found that the declined cell viability and elevated expression level of creatine kinase myocardial band (CK-MB) were observed in the H/R group, accompanied by the increased mitochondrial reactive oxygen species (ROS), elevated cellular malondialdehyde (MDA) level, and mitochondrial dysfunction. After Sitagliptin treatment, the damages in H9c2 cardiomyocytes, oxidative stress, and mitochondrial dysfunction were significantly alleviated. In addition, the overactivated autophagy and mitophagy in H/R-challenged cardiomyocytes were dramatically mitigated by Sitagliptin, accompanied by the upregulation of SIRT3. Lastly, the protective effect of Sitagliptin on H/R-induced mitophagy, autophagy, and damages in cardiomyocytes was dramatically abolished by the knockdown of SIRT3. Taken together, our data reveal that Sitagliptin ameliorated the H/R-induced injury in cardiomyocytes by mediating sirtuin 3 (SIRT3) and autophagy. Graphical abstract: uf0001